Patógenos periodontais: comparação entre cultura bacteriana e PCR em tempo real para teste diagnóstico - Bedran, Telma B. L. [UNESP] (2010)
The correct distinguishment of microorganisms involved in the periodontal disease pathogen, it is important in the understanding of its progression and adequate treatment planning. Considering this fact, some molecular methods of identification and quantification were developed and are extremely sensitive and precise in the characterization of different bacteria species. The present study aimed to realize a literature review, including studies that realized a comparative analysis between bacterial culture and real time PCR methods in the identification of pathogens. The bacterial culture method can possibly identify new microorganisms and realize antibiotics sensitivity tests. The real time PCR is a microbiologic test that identifies and quantifies bacterial species, through gene amplification of predetermined DNA fragments, with high sensitivity and specificity, and need a shorter operation time of the operator when compared to the bacterial culture method. In this way, to determine a specific diagnostic test, should be considered not only its precision in the identification of microorganisms, but the cost-benefit relationship as well.